Inspiratory Muscle Strength in Chagas Cardiomyopathy: A Systematic Scoping Review - Mazzoli-Rocha, Flavia (2023)
Fundação Oswaldo Cruz. Instituto Nacional de Infectologia Evandro Chagas. Laboratório de Pesquisa Clínica em Doença de Chagas. Rio de Janeiro, RJ, Brasil.